Comparative investigation of bio-beneficiation of Kasnau-Matasukh lignite using native microorganisms. Issue 7 (3rd July 2022) - Kumar, Aniruddha; Rajak, Pramod K; Singh, Asha Lata; Kumar, Rajesh; Singh, K N; Singh, Prakash K
ABSTRACT: In the present investigation, an attempt has been made to beneficiate lignite using Burkholderia sp. GR 8–02, Bacillus sp. XQW, and mixed consortium. The experiments showed that Bacillus sp. XQW could remove 18.18–37.50% of total sulfur followed by mixed consortium (18.18–29.17%) and Burkholdria sp. GR 8–02 (9.09%-29.17%). There was also a concomitant decrease in the content of mineral matter as revealed in decrease of ash yields from 10.02 to 29.12% by Bacillus sp. XQW followed by 11.74–29.10% by Burkholderia sp. GR8-02 and 9.93–29.30% by mixed consortium. During the biotreatment of lignite, a reduction in the volatile matter and oxygen was also observed. Study through Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), scanning electron microscopy–energy dispersive spectroscopy (SEM-EDS), petrography, and chemistry of lignite samples provided more insights into the changes in the calorific values as well as the chemical attributes of the lignite after bacterial treatment. The study revealed an increase in the Gross calorific value (6417–7234 cal/g) and Net calorific value (6522–7190 cal/g) of the lignite following the bacterial treatment. Thus, bacterial treatment of the lignite samples proved to be an effective tool for the upgradation of lignite.